Transition metal-free selective C–S bond cleavage of Ugi-adducts for rapid preparation of peptidomimetics. Issue 7 (15th March 2022) - Liu, Chao; Song, Liangliang; Peshkov, Vsevolod A.; Van der Eycken, Erik V.
Abstract : Diverse peptidomimetics containing N, O - or N, S -aminals are synthesized via a transition metal-free C–S bond cleavage and subsequent Mannich reaction. Abstract : A transition metal-free C–S bond cleavage and subsequent Mannich reaction of Ugi-adducts with alcohols as well as thiols is developed. Diverse novel peptidomimetics containing N, O - or N, S -aminals are synthesized in a rapid, highly efficient and step-economical fashion. This method features exclusive selectivity, broad substrate scope, excellent yield and functional group tolerance, and was applied on substrates derived from the pharmaceuticals febuxostat, probenecid and memantine.